THE EFFECT OF CHIA AND SESAME FLOUR SUBSTITUTION TO NUTRIENT CONTENT AND SENSORY QUALITY OF MINI CROISSANT - Mira Sofyaningsih; Imas Arumsari (Jurnal Pangan dan Agroindustri, 2021)
The use of flour made from sesame seed and chia seed could be applied into bakery products, such as croissant which made into â€œminiâ€ form fits for one bite-size. Sesame flour contains considerable amount of calcium, fiber, and essential fatty acids compared to wheat flour. Chia flour also can be used as a substitution along with sesame flour as it is one source of linoleic acid. This study aims to develop a substituted mini croissant with added nutrient value and sensory acceptable. This is an experimental study with three levels of flour substitution (0%, 10%, and 20%), each experiment was performed duplicate with sesame flour and chia flour ratio was set at 1:2. The results showed that sesame and chia flour substitution significantly increased the fiber and calcium content of mini croissant, but not the carbohydrate content. Substitution significantly affected sensory profile, both for hedonic test and sensory quality.